2012
DOI: 10.1179/1743282012y.0000000019
|View full text |Cite
|
Sign up to set email alerts
|

New national and regional bryophyte records, 32

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 58 publications
0
15
0
1
Order By: Relevance
“…The species richness of mosses in the study area is very high; 40% of the total of 766 species and infra-specific taxa reported from Borneo and 47% of the total of 651 species and infra-specific taxa reported from Sabah (Andi and Suleiman 2005, Suleiman et al 2006, 2009, 2011a, 2011b, 2017, Suleiman and Akiyama 2007, Higuchi et al 2008, Akiyama 2010, Ho et al 2010, Ellis et al 2010, 2015, 2016a, 2016b, Andi et al 2015, Chua and Suleiman 2015, Mohamed et al 2010, Suleiman and Rimi 2016). …”
Section: Resultsmentioning
confidence: 88%
“…The species richness of mosses in the study area is very high; 40% of the total of 766 species and infra-specific taxa reported from Borneo and 47% of the total of 651 species and infra-specific taxa reported from Sabah (Andi and Suleiman 2005, Suleiman et al 2006, 2009, 2011a, 2011b, 2017, Suleiman and Akiyama 2007, Higuchi et al 2008, Akiyama 2010, Ho et al 2010, Ellis et al 2010, 2015, 2016a, 2016b, Andi et al 2015, Chua and Suleiman 2015, Mohamed et al 2010, Suleiman and Rimi 2016). …”
Section: Resultsmentioning
confidence: 88%
“…The type, from Bolivia, is much like the widespread analog of P. denticulatum that occurs in Mexico, a species formerly known as P. drepanophyllum (Buck and Ireland, ; Buck, ) and currently as P. standleyi E.B. Bartram (Ochyra and Buck, ; Ochyra in Ellis et al., ). This species is characterized by plants with a loose foliation, a light green color and striate capsules.…”
Section: Discussionmentioning
confidence: 95%
“…It has maximum occurrence in subantarctic South Georgia and in Îles Kerguelen, and occasionally penetrates to Tierra del Fuego and the South Shetland Islands in the maritime Antarctic (Ochyra, 1998;Ochyra et al, 2008). Recently, the species was found on Heard Island (Ellis et al, 2010), and above it is recorded from Îles de la Possession, the largest island in the Îles Crozet archipelago. The species appears to be very rare on this island and only one small population was discovered, but the plants produced sporophytes in abundance.…”
Section: Bucklandiella Membranacea (Mitt) Bednarek-ochyra and Ochyramentioning
confidence: 99%